The impact of voltage unbalance and regulation on the life expectancy of LV induction machines - Mponwana, Samuel (Department of Electrical Engineering, 2020)
The induction machine is the most widely used electrical machine in the world, they are used for industrial, commercial and industrial applications. When manufactured they have nameplate ratings that stipulate the voltages and currents at which they may be operated. The quality of supply from power utilities can lead to them being operated under unbalanced voltage conditions. Power utilities experience voltage unbalances and voltage dips when they provide services to end users. In South Africa ESKOM is the primary power utility, it has a license agreement with NERSA stipulating the allowable voltage levels. In most cases the operating levels are within the agreed limits however many consumers are exposed to voltage levels at the fringe of these specified limits. This can be detrimental to electrical equipment if operated under these conditions for considerable lengths of time. NRS048 part 2 provides limits for voltage regulation and voltage unbalance which can exist on the power network at various voltage levels. It is incumbent on each utility to ensure that the quality of power supplied to end users complies with the minimum standards specified in the NRS048. Most customers connected to rural 11/22kV networks are farmers, where a large portion of the load is pumps driven by low voltage AC induction motors. NRS048 dictates the voltage limits as ±10% of the nominal supply voltage of 400V. The voltage unbalance on three phase systems is limited to 2%, and 3% for predominantly single-phase systems. Utilities such as Eskom have standards and operating procedures in place to run the networks optimally within these limits. Variations in the voltage levels on rural networks can be significant during load changes. Voltage unbalance levels can also be high due to the use of single-phase loads on these networks. Normally, utilities have operating procedures in place to allow operation of the supply network within the limits specified in the NRS048. Although these operating levels are within specified limits, a large portion of the customer’s plant can however be exposed to voltage levels well above or below the rated value of the equipment. Operating under these conditions can eventually lead to failure of the customer equipment. The impact of operating AC motors with voltages levels above or below the rated levels has not been fully determined on rural networks in South Africa. Research is therefore required to assess the impact of these operating conditions on customer equipment in rural areas and whether utility operating procedures need to be revised to take into consideration customer equipment. This has consequences for Eskom Distribution that relates to: a) The way in which the network voltages are managed, and b) Claims lodged against the Distribution business resulting from damage to customer’s motors The purpose of this research project is to investigate and quantify the impact of voltage regulation (over and under) and unbalance conditions on a typical rural feeder on the lifespan of induction machines. There are various definitions of voltage unbalance by NEMA, the IEC and the IEEE. The IEC definition is used in this research report, it is known as the true definition and incorporates both magnitude and phase information. To estimate the loss of life in induction machines operating under unbalanced conditions, the positive and negative sequence per phase equivalent circuits must be determined and the thermal model needs to be obtained and quantified as well. The losses obtained from the per phase sequence circuits are inputs to thermal model which in turn is used to predict the induction machine stator windings temperatures. Factors that are considered when analysing the impact of voltage unbalance and regulation on the life expectancy of machines include, the induction machine manufacturer, the size of the induction machine, the voltage rating of the induction machine and the efficiency class of the induction machine. The research presented in this report is primarily focused on the impact of voltage unbalance and regulation on the life expectancy of low voltage induction machines. The operating conditions considered in this report are prevalent on a typical rural feeder. Most customers connected to rural 11/22kV networks are farmers and a large portion of load pumps are driven by low voltage induction machines. This report presents the effect of these operating conditions on the life expectancy of the machines. The thermal model presented is suitable for continuously operated machines (S1). Since the operating conditions considered are primarily prevalent on typical rural feeders, the machines considered were also the machines primarily used in those regions. This has consequence that relates to the way in which the network voltages are managed, and claims lodged against power utilities resulting from damage to end user’s induction machines. The thermal model presented in this report can be incorporated as an algorithm and be implemented in microprocessor devices which enhance the level of accuracy and flexibility. As a practical application of the thermal model real time data can be processed according to the firmware thermal algorithm program and results are compared with the expected values and stored in memory. If a machine protection device is used, it computes an analog value which is then compared with the output of the thermal model algorithm. In practice the MPD usually triggers the digital outputs if the compared analog values exceed the set thermal threshold.